A Pre-Diagnosis Model for Indoor Radon Potential Assessment - Meneses, Paulo (2023)
Indoor radon is a well-known public health threat. WHO estimates radon causes between 3-14% of all lung cancers and has issued many recommendations to encourage countries to act against the exposure to radon and associated cancer risks. However, many people continue to be unaware about radon health risk. In previous works we developed a prediagnosis approach to evaluate the radon potential in indoor environments and motivate the citizens to act when the estimated radon potential is higher. In this work, we have developed an automatic classification model for the evaluation of the radon potential level in indoor environments by considering a set of relevant features selected to characterize occupants' risk exposure. Radon data measurements from previous works have been merged and provide enough data for the start of this project. The evaluation metrics of the obtained classification model are compelling and represent a good starting point for the development of a platform that will help to raise awareness of the radon risk and promote radon measurements to the wider population. These measurements will be used as new data for the generation of more robust classification models.